Pembelajaran Membaca dan Menulis Bahasa Arab di MA Sunan Pandanaran (Tinjauan Psikologi Perkembangan Linguistik Remaja) - Al Mubarokah, Zakiyatunnisa (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2020)
This study aims to describe planning, implementation, evaluation of Arabic learning and their compatibility with the psychology of adolescent linguistic development in class XI of religious programs Sunan Pandanaran Islamic high school. This type of research is field research with qualitative descriptive methods. The result of the study indicate that the (1) Arabic reading and writing skills includes the preparation of a syllabus and plans for implementing learning at the beginning of the learning year. (2) The implementation of learning is carried out in three activities, namely the initial ativity (introduction), the core activities (exploration, elaboration and confirmation), and closing activities. (3) Learning evaluation includes implementation techniques, instruments and follow-up from the evaluation results. (4) comparative results state that the palnning, implementation and evaluation as a whole are in accordance with the psychology of adolescent linguistic development